Is chlorophyll‐a the best surrogate for organic matter enrichment in submicron primary marine aerosol?. Issue 10 (28th May 2013) - Rinaldi, Matteo; Fuzzi, Sandro; Decesari, Stefano; Marullo, Salvatore; Santoleri, Rosalia; Provenzale, Antonello; von Hardenberg, Jost; Ceburnis, Darius; Vaishya, Aditya; O'Dowd, Colin D.; Facchini, Maria Cristina
Abstract: [1] Initial efforts toward developing a combined organic‐inorganic sea spray source function parameterization for large‐scale models made use of chlorophyll‐ a (Chl‐ a ) and wind speed as input parameters to combine oceanic biology and atmospheric dynamics. These studies reported a modest correlation coefficient (0.55) between chlorophyll‐ a and organic matter (OM) enrichment in sea spray, suggesting that chlorophyll‐ a is only partially suitable for predicting organic enrichment. A reconstructed chlorophyll‐ a field of the North Atlantic Ocean from GlobColour reveals an improved correlation of 0.72 between the fractional mass contribution of organics in sea spray and chlorophyll‐ a concentration. A similar analysis, using colored dissolved and detrital organic material absorption and particulate organic carbon concentration, revealed slightly lower correlation coefficients (0.65 and 0.68). These results indicate that to date, chlorophyll‐ a is the best biological surrogate for predicting sea spray organic enrichment. In fact, considering the minimal difference between the correlation coefficients obtained with the three ocean color products, there is no reason to substitute chlorophyll‐ a, which is the most accurate parameter obtained from ocean color data, with other biological surrogates being generally affected by larger and less known errors. The observed time lag between chlorophyll‐ a concentration and organic matter enrichment in aerosol suggests that biological processes in oceanic surface waters and their timescales should be considered when modeling the production of primary marine organic aerosol. Key Points: Chlorophyll is the best proxy for predicting marine primary organic aerosol A new relationship describing the organic enrichment of sea spray is presented